Methodological Proposal to Correct and Adjust a Geodesic Leveling Data - Guevara Lima, José Ricardo; González Giraldo, Sandra Milena; Sánchez Cárdenas, Juan Sebastián (TECCIENCIA, 2019)
The objective of the work is to standardize the method by which the corrections are calculated and applied to make the adjustment to the geometric leveling data obtained in ground. For this purpose, was consulted related bibliography and two methodologies were obtained: one for the corrections, taking into account the National Oceanic and Atmospheric Administration (NOAA) technical norm of the United States, and one for the adjustment, based on the minimum method Squares correlated, exposed by the Cartographic Agency of the United States Department of Defense. The proposed methodology, generated by the geodesic leveling seedlings of the Geodesy Internal Geodesy Working Group of the Instituto Geográfico Agustín Codazzi (IGAC), was evaluated by its application to the ground data obtained in a leveling circuit located in the department of Cesar, Colombia, and satisfactory results were obtained.